2012
DOI: 10.1021/ol302022y
|View full text |Cite
|
Sign up to set email alerts
|

Tröger’s Base Twisted Amides: Endo Functionalization and Synthesis of an Inverted Crown Ether

Abstract: Taking advantage of the unconventional reactivity of twisted mono- and bis-amides of Tröger's base (TB), rac-6 and rac-7, respectively, the first synthesis of a 6-endo-monosubstituted TB analogue, rac-9, and the first rational synthesis of a 6,12-endo,endo-disubstituted TB analogue, rac-11, have been achieved. The bis-TB crown ether, meso-13, was prepared starting from rac-7. Meso-13 constitutes a rare example of a crown ether with an inverted methylene bridge-to-bridge bis-TB conformation both in solution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 65 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…Nevertheless, this type of reactivity could be very useful in more complicated systems, such as Tröger bases, in which the benzylic positions can be lithiated in a straightforward fashion with s BuLi (Figure 2 a, 58 ). The exo ‐selective installation of an amino‐terminated chain on a Tröger base scaffold in high yield provided a very versatile handle for its further functionalization 20. In addition to carbon nucleophiles, the lithium salt of diphenylamine also reacted smoothly to afford the hydroxylamine derivative (see the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, this type of reactivity could be very useful in more complicated systems, such as Tröger bases, in which the benzylic positions can be lithiated in a straightforward fashion with s BuLi (Figure 2 a, 58 ). The exo ‐selective installation of an amino‐terminated chain on a Tröger base scaffold in high yield provided a very versatile handle for its further functionalization 20. In addition to carbon nucleophiles, the lithium salt of diphenylamine also reacted smoothly to afford the hydroxylamine derivative (see the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[23] This methodology elegantly exploits the high electrophilicity of the carbonyl group in twisted amides,p roviding direct access to stereochemically defined Trçger's base derivativesa fter hydrogenation. [23] This methodology elegantly exploits the high electrophilicity of the carbonyl group in twisted amides,p roviding direct access to stereochemically defined Trçger's base derivativesa fter hydrogenation.…”
Section: Trçger's Base Twistedamidesmentioning
confidence: 99%
“…Subsequently, these authors reported the Wittig reaction using Ph 3 P=CHCO 2 Et and mono‐ and bis‐twisted amides (Scheme B) . This methodology elegantly exploits the high electrophilicity of the carbonyl group in twisted amides, providing direct access to stereochemically defined Tröger's base derivatives after hydrogenation.…”
Section: Twisted Amides: New Frontiersmentioning
confidence: 99%
“…397–398 Kirby demonstrated that 1-aza-2-adamantanone undergoes the Wittig reaction to give a bridged enamine under standard conditions employed for olefination of ketones (Scheme 149a), 108 Aubé utilized a Petasis olefination to afford exo-cyclic enamine with a [4.3.1] ring system (Scheme 149b), 408 while Wärnmark functionalized Tröger’s base-derived bridged lactams using the less reactive carbethoxymethylene-triphenylphosphorane under thermal conditions (Scheme 149c). 316 …”
Section: Reactivity Of Bridged Lactams and Related Heterocyclesmentioning
confidence: 99%